Clinical significance of personalized excision of AALTF in progressive collapse foot deformity: a retrospective cohort study - Liu, Shangyi; Shu, Xun; Wang, Bin; Yang, Huarui; Yang, Yi; Bao, Tongzhu; Ye, Tao; Shou, Kangquan (Frontiers in Surgery, 2025)
BackgroundIt has been suggested that an accessory anterolateral talar facet (AALTF) is likely to produce accessory talar facet impingement (ATFI), resulting in sinus tarsi pain in patients with progressive collapse foot deformity. However, the appropriate strategy for AALTF is not well documented. The aim of this study is to evaluate the relationship between the ATFI and AALTF in patients with progressive collapse foot deformity and elucidate the optimal treatment approach for AALTF.MethodsSeventy patients with progressive collapse foot deformity who underwent surgery between March 2014 and October 2024 were included and split into two groups: the AALTF resection group (AALTF resection alongside concomitant flatfoot procedures) and the traditional group (only flatfoot procedures were performed). All patients underwent radiographic evaluation and completed Foot Functional Index (FFI), American Orthopedic Foot and Ankle Society (AOFAS), and Foot and Ankle Ability Measure-Sports Subscale (FAAM-SS) assessments preoperatively and again at follow-up within 24 months.ResultsThe AALTF resection group showed significant improvements in clinical outcome measures compared to the traditional treatment group. The AALTF resection group demonstrated higher FFI scores (preoperative mean: 41.2 ± 11.4, postoperative mean: 9.3 ± 10.6) compared to the traditional group (preoperative mean: 42.1 ± 10.7, postoperative mean: 16.6 ± 4.5; p < 0.001). The AALTF resection group also demonstrated higher AOFAS scores (preoperative mean: 67.3 ± 14.7, postoperative mean: 92.7 ± 8.6) compared to the traditional group (preoperative mean: 68.2 ± 13.8, postoperative mean: 81.5 ± 9.1; p < 0.001). FAAM-SS scores were higher in the AALTF resection group (preoperative mean: 39.6 ± 11.6, postoperative mean: 90.6 ± 11.3) than in the traditional group (preoperative mean: 44.7 ± 12.3, postoperative mean: 80.9 ± 5.1; p < 0.001). Ankle joint ROM improved more markedly in the AALTF resection group at final follow-up (preoperative mean: 7.3° ± 2.1° to postoperative mean: 19.6° ± 3.8°) than in the traditional group (preoperative mean: 8.7° ± 1.6° to postoperative mean: 14.1° ± 2.2°; p < 0.001). There were no significant differences in radiological outcomes between the two groups.ConclusionsAddressing AALTF in a symptomatic flatfoot is fundamental. A careful preoperative assessment, consisting of traumatic history investigation, deliberate physical examination, and standard radiographic evaluation (especially CT and MRI scan), can help determine the most appropriate strategy for this kind of morbidity.